2020
DOI: 10.1182/bloodadvances.2020002178
|View full text |Cite
|
Sign up to set email alerts
|

Five decades of low intensity and low survival: adapting intensified regimens to cure pediatric Burkitt lymphoma in Africa

Abstract: Long-term cure of childhood Burkitt lymphoma (BL) in sub-Saharan Africa after treatment with single-agent cyclophosphamide has been documented for more than half of a century. Contemporary cure rates for the highest-risk patients with BL in high-income countries exceed 90% using intensive multiagent chemotherapy. By contrast, the majority of African children with BL still die. Data spanning 5 decades in Africa have repeatedly shown that the children most likely to achieve cure with limited cyclophosphamide reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 84 publications
0
32
0
Order By: Relevance
“…Nonetheless, EBV is associated with 200,000 human cancers per year, including Burkitt lymphoma, posttransplant lymphoproliferative diseases, Hodgkin lymphoma, and gastric and nasopharyngeal carcinoma ( 1 , 2 ). Endemic Burkitt lymphoma caused by EBV remains the most common childhood cancer in sub-Saharan Africa ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, EBV is associated with 200,000 human cancers per year, including Burkitt lymphoma, posttransplant lymphoproliferative diseases, Hodgkin lymphoma, and gastric and nasopharyngeal carcinoma ( 1 , 2 ). Endemic Burkitt lymphoma caused by EBV remains the most common childhood cancer in sub-Saharan Africa ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The report from Hong Kong using plasma EBV DNA screening for nasopharyngeal carcinoma suggested that screening of high risk populations facilitated earlier diagnosis and resulted in increased survival rates. In this regard, we note that the cure rate for pediatric BL in high resource settings with chemotherapy is >90% ( 20 , 21 ). However, in limited resource settings, the cure rate for endemic BL is much lower—44% in a recent report from Uganda ( 22 ).…”
Section: Discussionmentioning
confidence: 88%
“…Most children diagnosed with non-Hodgkin lymphoma (NHL) in high-income countries are expected to achieve long-term survival; however, children in lower income countries are diagnosed with NHL at a disproportionally higher rate and do not experience the same chance for cure. [1][2][3][4][5][6][7][8][9][10] This disparity is related to many factors, including late disease detection and challenges in delivering high-intensity treatment, such as methotrexate. [3] High-dose methotrexate (HD-MTX; 1-8 g/m 2 ) is an essential component of pediatric mature B-cell and T-cell NHL treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] This disparity is related to many factors, including late disease detection and challenges in delivering high-intensity treatment, such as methotrexate. [3] High-dose methotrexate (HD-MTX; 1-8 g/m 2 ) is an essential component of pediatric mature B-cell and T-cell NHL treatment. [11] The use of HD-MTX in lower income countries has been challenging due to treatment-related mortality at doses of 1-2 g/m 2 , yet even higher doses are needed to adequately treat NHL.…”
Section: Introductionmentioning
confidence: 99%